Quality management handbook - Kimber, Raymond J.; Grenier, Robert W.; Heldt, John Jourdan (Quality and reliability, 1997)
Affords an advantageous understanding of contemporary management and total quality systems without excessive employment of advanced mathematics--directing managers in the implementation of the basic quality framework that will lead to improved production and increased profits through sound quality practices. Provides practical applications in a wide variety of industrial, financial, service, and administrative systems and shows how to prepare for quality audits, product meetings, and production discussions. Features 21 new chapters